'Women-protective' language as a tool of exclusion: Debates on oocyte donation in Latvia. Issue 4 (November 2019) - Mezinska, Signe; Mileiko, Ilze
'Women-protective' language is broadly used as a frame in political discussions on women's reproductive healthcare and labour rights. This article addresses the use of 'women-protective' language in online news articles in the Latvian media about the proposed prohibition of oocyte donation for nulliparous women. The main focus of the recent Latvian debate has not been on the technology itself, but rather on the female body and women's rationality and decision-making capacity. The results of the analysis show that use of the 'women-protective' frame positions women as victims, increases control over the female body and restricts women's rights to make autonomous decisions. The application of this frame is especially dangerous when used by politicians as it may lead to the legal restriction of women's rights.